Prevalence and risk factors of antibodies to HLA according to different cut‐off values of mean fluorescence intensity in haploidentical allograft candidates: A prospective study of 3805 subjects. (21st June 2022) - Ma, Ning; Guo, Jia‐Pei; Zhao, Xiang‐Yu; Xu, Lan‐Ping; Zhang, Xiao‐Hui; Wang, Yu; Mo, Xiao‐Dong; Zhang, Yuan‐Yuan; Liu, Yan‐Rong; Zhao, Xiao‐Su; Cheng, Yi‐Fei; Liu, Kai‐Yan; et al.
Abstract : The importance of anti‐HLA antibodies in transplantation settings, such as HLA‐mismatched or haploidentical hematopoietic stem cell transplantation and platelet refractoriness, is widely recognized. In previous reports, it was mentioned that several cut‐off values of donor‐specific anti‐HLA antibodies mean fluorescence intensity (MFI) were related to graft rejection in the environment of HLA mismatched stem cell transplantation and the aim of this study was to investigate the prevalence and risk factors of anti‐HLA antibodies according to those cut‐off values of MFI. A total of 3805 patients with hematologic disease were prospectively enrolled and analyzed. When using MFI of anti‐HLA antibodies ≥500, ≥1000, ≥1500, ≥2000, ≥5000, and ≥ 10, 000 as cut‐off values for positivity, the prevalence of class I or II anti‐HLA antibodies ranged from 4.6% to 20.2% in all cases. When the MFI cut‐off value was ≥500 for positivity, multivariate analysis indicated that platelet transfusion, underlying disease, and pregnancy were the most important risk factors for the presence of anti‐HLA antibodies for the total patients. Subgroup analysis according to age, gender, and underlying disease showed that pregnancy was the most important risk factor for the presence of anti‐HLA antibodies. For all patients ( n = 3805), when anti‐HLA antibody positivity was defined according to different MFI cut‐off values, including ≥1000, ≥1500, ≥2000, ≥5000, and ≥ 10, 000, an association of platelet transfusion and pregnancy with anti‐HLA antibodies was also demonstrated. Our results suggest that pregnancy and platelet transfusion are the main risk factors for the prevalence of anti‐HLA antibodies in haploid allograft candidates, providing evidence for guiding the evaluation of anti‐HLA antibodies and helping donor selection for HLA‐mismatched transplant candidates.